Comparison of pneumatic compression device and sand bag with respect to peripheral vascular complications in elective cardiac catheterization and percutaneous femoral artery interventions - Feyzullah Beşli; Mehmet Fethi Alişir; Mesut Kecebaş; Osman Akın Serdar; Fatih Güngören (KARE Publishing, 2013)
Objectives: After coronary angiography and percutaneous coronary intervention (PCI), the classic sand bag method and compression devices are widely used for control of bleeding and prevention of vascular complications. The purpose of our study was to assess the major peripheral vascular complications and to compare the sand bag and a pneumatic compression device ('Close Pad') in terms of major peripheral vascular complications after coronary interventions. Study design: Between June 2011 and November 2011, a total of 434 patients who admitted to the Department of Cardiology of Uludag University Faculty of Medicine were included in the study. 396 patients underwent coronary angiography and 38 patients underwent PCI. Sand bag was applied in 209 patients. Bleeding requiring transfusion, hematoma larger than 10 cm², pseudoaneurysm, and arteriovenous (AV) fistula were defined as the major local complications. Logistic regression analysis were used to evaluate the datas. Results: Major vascular complications occurred in 2% of diagnostic angiography and in 13.2% of PCI patients (p=0.003). The major vascular complications were significantly higher with the Close Pad device compared with sand bag (5.3% vs. 0.5%, p=0.007). Smoking, PCI, Close Pad, clopidogrel, and anticoagulants were observed to have increased risk of major local complications. In the logistic regression analysis, only smoking and Close Pad usage were evaluated as independent variables that increased the risk of major vascular complications (p<0.05). Conclusion: Close Pad usage demonstrated increased risk of vascular complications when compared with the sand bag in patients undergoing cardiac catheterizations. After the PCI, patients should be selected carefully for application of the Close Pad.